Political Strategies in Pre-Columbian Mesoamerica - Baron, Joanne; Kurnick, Sarah (Book collections on Project MUSE., 2016)
"Political authority contains an inherent contradiction. Rulers must reinforce social inequality and bolster their own unique position at the top of the sociopolitical hierarchy, yet simultaneously emphasize social similarities and the commonalities shared by all. Political Strategies in Pre-Columbian Mesoamerica explores the different and complex ways that those who exercised authority in the region confronted this contradiction. New data from a variety of well-known scholars in Mesoamerican archaeology reveal the creation, perpetuation, and contestation of politically authoritative relationships between rulers and subjects and between nobles and commoners. The contributions span the geographic breadth and temporal extent of pre-Columbian Mesoamerica--from Preclassic Oaxaca to the Classic Peten region of Guatemala to the Postclassic Michoacan--and the contributors weave together archaeological, epigraphic, and ethnohistoric data. Grappling with the questions of how those exercising authority convince others to follow and why individuals often choose to recognize and comply with authority, Political Strategies in Pre-Columbian Mesoamerica discusses why the study of political authority is both timely and significant, reviews how scholars have historically understood the operation of political authority, and proposes a new analytical framework to understand how rulers rule. Contributors include Sarah B. Barber, Joanne Baron, Christopher S. Beekman, Jeffrey Brzezinski, Bryce Davenport, Charles Golden, Takeshi Inomata, Arthur A. Joyce, Sarah Kurnick, Carlo J. Lucido, Simon Martin, Tatsuya Murakami, Helen Perlstein Pollard, and Victor Salazar Chavez"--